The combination of drought and heat stress has a greater effect on potato plants than single stresses - Tri Handayani; Kazuo Watanabe (Plant, Soil and Environment, 2020)
Several research groups have examined the effects of drought stress and heat stress on potato, but few investigations of the effects of combined drought-heat stress have been reported. Using five potato lines, the potato plants' responses to drought stress, heat stress, as well as combined drought-heat stress were studied, to get the insight in phenotypic shift due to abiotic stresses. The experiment was conducted as a growth room experimental under non-stress and abiotic stresses (drought, heat, and combined drought-heat) conditions. The results demonstrated that potato plants responded to the abiotic stresses by decreasing their plant height, leaf size, cell membrane stability, and relative water content (RWC). However, increasing their leaf chlorophyll content under drought and combined drought-heat stresses. Generally, the combined drought-heat stress had a greater effect on the tested traits. The potato line L1 (84.194.30) showed the lowest level of wilting in all three types of abiotic stress, supported by a small RWC change compared to the control condition; L1 is thus considered relatively tolerant to abiotic stress. The potato lines' different responses to each type of abiotic stress indicate that the potato lines have different levels of sensitivity to each abiotic stress.